2012
DOI: 10.1021/ja303131j
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Road for the Transformation of Few-Layer Graphene into MWNTs

Abstract: We report the direct formation of multiwalled carbon nanotubes (MWNT) by ultrasonication of graphite in dimethylformamide (DMF) upon addition of ferrocene aldehyde (Fc-CHO). The tubular structures appear exclusively at the edges of graphene layers and contain Fe clusters. Fc in conjunction with benzyl aldehyde, or other Fc derivatives, does not induce formation of NT. Higher amounts of Fc-CHO added to the dispersion do not increase significantly MWNT formation. Increasing the temperature reduces the amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 46 publications
2
66
0
2
Order By: Relevance
“…The U/Ms were not part of the layer structure, but rather a unique hybrid structure of onedimensional (1D) nanotubes and two-dimensional (2D) UMCNOs. 31,33,43,56 In addition, the peaks at 22.2°and 26.1°a lso demonstrate the coexistence of MWNTs and UMCNOs. Raman spectroscopy was also applied to characterize the U/ Ms. As shown in Figure 4, the D and G bands of MWNTs at 1338 and 1569 cm −1 are attributed to the defects and disorderinduced modes and the in-plane E 2g zone-center mode, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…The U/Ms were not part of the layer structure, but rather a unique hybrid structure of onedimensional (1D) nanotubes and two-dimensional (2D) UMCNOs. 31,33,43,56 In addition, the peaks at 22.2°and 26.1°a lso demonstrate the coexistence of MWNTs and UMCNOs. Raman spectroscopy was also applied to characterize the U/ Ms. As shown in Figure 4, the D and G bands of MWNTs at 1338 and 1569 cm −1 are attributed to the defects and disorderinduced modes and the in-plane E 2g zone-center mode, respectively.…”
Section: Resultsmentioning
confidence: 93%
“…542 The mechanism of carbon nanotube formation from graphene using this approach is shown in Figure 77. 542 Ultrasonication in dimethylformamide disrupts the graphene structure, causing it to break up into small fragments due to the oxidation of radical species at the sheet's edges and inner defect sites.…”
Section: Interconversions Of Carbonmentioning
confidence: 99%
“…This mechanism could potentially be exploited to produce nested multiwalled nanotubes having chiralities different from those obtained using stochastic synthetic processes. 542 It has recently been shown that single-layered and multilayered graphenes are readily converted into other carbon nanostructures by treatment with a high-energy electron beam. 543,544 This process imposes strain on chemical bonds, causing them to stretch (i.e., it induces localized bond deformations), promoting the conversion of graphene into other carbon allotropes.…”
Section: Interconversions Of Carbonmentioning
confidence: 99%
“…Concurrent with unique electronic properties, the appropriate layer spacing of nanoscrolls might allow for energy storage applications 8,9 . Despite fascinating properties and a handful of theoretical studies of graphene nanoscrolls [10][11][12][13][14] , only few experimental studies [15][16][17][18] are reported for rGOx nanoscrolls. Viculis et al 17 showed that exfoliation of graphite by alkali metals followed by very strong sonication led to the formation of nanoscrolls, whereas Wang et al 18 showed that the aggregation of Ag particles on graphene sheets together with high-power sonication initiated the rolling of the rGOx nanoscrolls.…”
mentioning
confidence: 99%